The influence of biosynthesis zinc oxide nanoparticles by using fruit extracts of ananas comosus towards the performance of PSF/ZNO membrane - Raja Ahmad, Raja Puteri Nurul Adibah (2020)
Severe drinking water shortage is a significant problem worldwide and now becoming a crucial issue in the field of water purification. The main key of this work is to enhance membrane performance permeability, rejection, anti-fouling and antibacterial activity. This study seeks to discover the influenced of biosynthesis of Zinc Oxide (ZnO) nanoparticles by using fruits extracts of Ananas Comosus towards the characteristic, properties and performance polysulfone (PSf) mixed matrix membrane. The biosynthesis ZnO, (ZnO (P)) nanoparticles powder was successfully synthesized by using fruit extracts of Ananas Comosus. The characterization and performance of the ZnO (P) were conducted in this study and compared with commercial ZnO, (ZnO (C)). In the beginning, the purity and crystallinity of the ZnO (P) powder was determined by using X-ray diffraction analysis (XRD) that showed the optimum synthesized composition peak was matched well with the ZnO (C) with crystallite size in the range of 12.2nm. The bandgap energy value of the ZnO (C) and ZnO (P) was 2.20 eV and 3.17 eV respectively which in line with the photocatalytic activity as many as 66.4% and 96.2% for ZnO (C) and ZnO (P) respectively in this study. The inhibition area of ZnO (P) nanoparticles powder is also relatively larger than ZnO (C) nanoparticles powder. All seven samples were successfully prepared via the phase inversion method. Obviously, the addition of ZnO nanoparticles in the PSf membrane has increased the membrane hydrophilicity property that strongly affected the membrane characteristic, property and performance. The hydrophilicity of the 3% ZnO (P) as compared to 0% ZnO and ZnO (C) increased up to 34.21% and 23.92% respectively which in line with the improvement of membrane morphology, surface roughness thus further enhanced the performance in term of permeability of the membrane. SEM results displayed that the addition of ZnO nanoparticles had enhanced the membrane porosity, reduced the tensile strength, increased in surface roughness as the additives increased up to 3% ZnO (P) which leads to enhance the antibacterial properties of the membrane. Membrane permeability was increased to 140.79% in 3% ZnO (P) compared to 0% ZnO. The antibacterial activity of the membrane with ZnO nanoparticle was improved especially with the presence of biosynthesis ZnO in 5% ZnO (P). The result also showed that the green reduction agent of ZnO had exceedingly affected the membrane characterisation and its performance. In conclusion, the addition of ZnO has increased the performance of the PSf membrane especially with the green synthesis reduction agent of Ananas Comosus in 3% ZnO (P).